1997
DOI: 10.1161/01.cir.96.8.2586
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Peripheral Chemosensitivity as a Potential Input to Baroreflex Impairment and Autonomic Imbalance in Chronic Heart Failure

Abstract: A link between increased peripheral chemosensitivity and impaired autonomic control, including baroreflex inhibition, is demonstrated. The clinical importance of this phenomenon warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
1
14

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(195 citation statements)
references
References 47 publications
7
173
1
14
Order By: Relevance
“…Metabolite accumulation as well as mechanical stimuli in the isometrically working muscle (muscle metaboreflex) can lead to an enhanced vascular response [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. This metaboreflex likely overrides the baroreflex, leading to a stronger sympathetic efferent activity to the vessels during ISO [46,47,53,[62][63][64][65][66]. Beside the BP response, that seems to evidence increased sympathetic efferent drive to the vessels during ISO, there was a significant increase of the log-power in the LF and HF range, whereas the normalized spectral power values were similar between the exercise modes.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite accumulation as well as mechanical stimuli in the isometrically working muscle (muscle metaboreflex) can lead to an enhanced vascular response [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. This metaboreflex likely overrides the baroreflex, leading to a stronger sympathetic efferent activity to the vessels during ISO [46,47,53,[62][63][64][65][66]. Beside the BP response, that seems to evidence increased sympathetic efferent drive to the vessels during ISO, there was a significant increase of the log-power in the LF and HF range, whereas the normalized spectral power values were similar between the exercise modes.…”
Section: Discussionmentioning
confidence: 99%
“…11 Subjects breathed spontaneously and were asked to relax, but not to fall asleep. Stationary, 20-minute periods of recording were selected, and autoregressive power spectral analysis was applied to the RR interval time series.…”
Section: Cardiac Autonomic Controlmentioning
confidence: 99%
“…Stationary, 20-minute periods of recording were selected, and autoregressive power spectral analysis was applied to the RR interval time series. 11 The following spectral bands of heart rate variability (HRV) were identified: low-frequency (0.04 to 0.15 Hz, LF) and high-frequency (0.15 to 0.40 Hz). The areas below each peak were calculated in absolute units (ms 2 ).…”
Section: Cardiac Autonomic Controlmentioning
confidence: 99%
“…In contrast, other authors [15][16][17] reported reduced HRV in CHF patients with a predominance of sympathetic activity. These authors suggest that sympathetic hyperactivity in HR control is a reflection of compensatory changes in the autonomic system caused by the evolution of the disease and aimed at ensuring homeostasis with an appropriate increase in cardiac output.…”
Section: Impact Of the Cardiorespiratory Diseases On Hrv At Restmentioning
confidence: 77%
“…Musialik-Lydka, Sreidniawa and Pasyk 12 , Tulppo and Huikuri 13 and Rosen et al 14 suggest the predominance of sympathetic activity in the sinus node. In contrast, van de Borne et al 15 , Ponikowski et al 16 and Mortara et al 17 observed the sympathovagal imbalance of the autonomic control of HR without evidence of sympathetic hyperactivity.…”
Section: Introductionmentioning
confidence: 91%